Impact of papilloscopic expert reports at crime sites on court decisions (Research, Society and Development, 2020)
This article proposes to verify the impact that the Papilloscopic Examination Reports of crime places, issued by the Papilloscopists of the Federal Police, produce or not in the respective decisions in the judicial processes. This is a quantitative and qualitative study, based on a census of papilloscopic crime scene reports produced from 2013 to 2016 in the Federal Police Superintendency in Belém-PA. The results showed that these technical documents had an impact in order to convince the Attorneys of the Republic and the Federal Judges that the individual indicated by this report, in fact, represents the perpetrator of the crime. As a consequence, the manifestations of the members of the Public Prosecutor's Office in favor of preventive detention are based on the individual described in the reports of papilloscopic expertise, as well as the complaints offered to the Justice. In the same way, the Federal Judges, in the judicial processes concerning these reports, decreed preventive detention and even condemned, in a judicial sentence, the persons indicated by these technical documents, confirming the repercussion of the reports in the judicial decisions.